2012
DOI: 10.1029/2012gl051120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of native forest restoration on soil hydraulic properties, Auwahi, Maui, Hawaiian Islands

Abstract: Over historic time Hawai‘i's dryland forests have been largely replaced by grasslands for grazing livestock. On‐going efforts have been undertaken to restore dryland forests to bring back native species and reduce erosion. The reestablishment of native ecosystems on land severely degraded by long‐term alternative use requires reversal of the impacts of erosion, organic‐matter loss, and soil structural damage on soil hydraulic properties. This issue is perhaps especially critical in dryland forests where the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 30 publications
3
44
0
1
Order By: Relevance
“…Perkins et al (2012) found that mean field-saturated hydraulic conductivity in newly restored forest cover with an abundance of preferential flow channels was greater by a factor of 2.0 compared with soils of rangelands. The percent preferentiality in the subsurface increased from an average 1.3 in grasslands to 2.6 in restored forest.…”
Section: Preferential Flow Paths and Shc And Sommentioning
confidence: 98%
See 1 more Smart Citation
“…Perkins et al (2012) found that mean field-saturated hydraulic conductivity in newly restored forest cover with an abundance of preferential flow channels was greater by a factor of 2.0 compared with soils of rangelands. The percent preferentiality in the subsurface increased from an average 1.3 in grasslands to 2.6 in restored forest.…”
Section: Preferential Flow Paths and Shc And Sommentioning
confidence: 98%
“…The effects of preferential flow pathways on SHC have been noted before (Price et al 2010). Perkins et al (2012) found that mean field-saturated hydraulic conductivity in newly restored forest cover with an abundance of preferential flow channels was greater by a factor of 2.0 compared with soils of rangelands.…”
Section: Preferential Flow Paths and Shc And Sommentioning
confidence: 99%
“…Wang et al (2012) found that soil moisture is lower under trees than grasslands and crops, while Perkins et al (2012) found subsurface wetting and hydraulic conductivity becomes higher in restored forest lands than grasslands and grazing lands. As the scale of watersheds is increasing, land use impacts on hydrology could be diluted (Blö schl et al, 2007).…”
Section: Small Watersheds/farm Level Effectsmentioning
confidence: 98%
“…In addition, effects on total flow and high flow are better understood than low flows (Eisenbies et al, 2007;Cui et al, 2012). Part of the difficulty in predicting low flows is the low accuracy of low flow measurement (Ratto et al, 2007), which could contribute to the complexity of the observed responses. High flows are also difficult to measure, but it is important to remember that it is the frequency of high flows which increases, with less certainty about the magnitude of the highest flows.…”
Section: B S T R a C Tmentioning
confidence: 99%
“…The low surface and near-surface K fs reported for grazing conditions is mostly the result of destroyed macroporosity through trampling by cattle and by the much diminished soil faunal activity after forest clearing and burning with the associated loss of topsoil organic matter and surface exposure with erosive precipitation (McIntyre, 1958a, b;Lal, 1988;Deuchars et al, 1999;Colloff et al, 2010;Bonell et al, 2010). Natural forest regrowth on degraded pasture or planting trees followed by uninterrupted plantation development can be expected to gradually improve the soil water intake capacity again through the steady incorporation of organic matter, soil faunal and insect burrowing activity, and root turnover (Gilmour et al, 1987;Bonell, 2005;Ilstedt et al, 2007;Bonell et al, 2010;Colloff et al, 2010;Hassler et al, 2011;Perkins et al, 2012). Conversely, impervious footpaths, yards and roads will remain runoff-producing features in post-forest landscapes (Ziegler et al, 2004;Rijsdijk et al, 2007) as well as in managed (forest) plantation areas (La Marche and Lettenmaier, 2001;Ziegler et al, 2007;Liu et al, 2009).…”
Section: Human Impact On Forest Hydrological Functioningan Understudimentioning
confidence: 99%